2020
DOI: 10.1016/j.indcrop.2020.112985
|View full text |Cite
|
Sign up to set email alerts
|

Growth years and post-harvest processing methods have critical roles on the contents of medicinal active ingredients of Scutellaria baicalensis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 68 publications
(69 reference statements)
2
29
0
Order By: Relevance
“…Scutellaria baicalensis , as a Chinese medicinal material, was traditionally used to treat lung and liver diseases in many Asian countries [ 40 ]. In recent years, Scutellariae Radix has been becoming one of the top ten sales of medicinal herbs in the Chinese medicine market because of its growing market demand every year and huge medicinal value [ 46 ]. R2R3-MYB proteins are involved in various plant biological processes including organ development processes, hormone synthesis and signal transduction, response to biotic and abiotic stresses, and primary and secondary metabolism, which were the main forms in all higher plants [ 4 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scutellaria baicalensis , as a Chinese medicinal material, was traditionally used to treat lung and liver diseases in many Asian countries [ 40 ]. In recent years, Scutellariae Radix has been becoming one of the top ten sales of medicinal herbs in the Chinese medicine market because of its growing market demand every year and huge medicinal value [ 46 ]. R2R3-MYB proteins are involved in various plant biological processes including organ development processes, hormone synthesis and signal transduction, response to biotic and abiotic stresses, and primary and secondary metabolism, which were the main forms in all higher plants [ 4 , 5 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all secondary metabolite levels increase with the growth age of the plant. Bai et al (2020) studied the content of eight active ingredients in the roots of Scutellaria baicalensis from 1 to 15 years and found that the trend of the content of four major medicinal ingredients showed a “V” type. In other words, 2-, 3-, and 15-year old S. baicalensis have a higher content of medicinal components than 4- and 5-year old ones.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalein is not only derived from traditional medicinal plants like root of Scutellaria baicalensis ( Bai et al, 2020 ) , but also is from foods in daily life ( Jin et al, 2017 ). So it is easy for us to automatically and consciously uptake a certain amount of baicalein.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidences showed wide pharmacological functions such as alleviation of oxidative stress and inflammation ( Yan et al, 2020 ), suppression of cancer ( He et al, 2021 ), protection of liver injury ( Dai et al, 2021 ). According to the literature of Bai, C. et al, the annual yield of Scutellaria baicalensis is over 10,000 tons, and the content of baicalein was approximately 7 mg/g in the dry roots of 2-year-old Scutellaria baicalensis ( Bai et al, 2020 ) . It was also used as a food condiment in our daily life.…”
Section: Introductionmentioning
confidence: 99%